Data Monitoring System for Micro-Wind Turbine Experimental Set Based on LabVIEW - Watjanatepin, Napat (International Journal of Engineering and Technology, 2018)
The Wind Turbine Energy System (WTES) was applied to a micro-scale laboratory experimental set. Thus, there is a need to develop a data monitoring system in order to be applicable with the Wind Turbine Energy System. The aim of this study is to design and develop the data monitoring system for the Micro-Wind Turbine (MWT) experimental set, and to test the real time output and analyse the obtained results. The MWT output power is 100 watts 12 VDC with the cut-in speed is 3 m/s. The WTES consists of MWT, DC converter, and a Grid-connected inverter.Â This data monitoring system will be based on LabVIEW environment. The NI-9215 NI-9226, NI 9203, NI 9225, NI 9401 with chassis NI 9178 data acquisition devices were applied. The data monitoring program was developed by LabVIEW2013. The LabVIEW based data monitoring system has successfully met the objective of this study. It is capable of providing real time acquisition of the wind speed, electrical current, voltage and power of the Micro-Wind Turbine Energy System. Moreover, the software can generate a report from the MySQL data based via Microsoft office automatically.Â Â Â Â Â